The child with pruritus: a challenge for the pediatrician. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2018)
The problem of pruritus in childhood was treated exclusively from a clinical point of view. The differences due to the age were first discussed. These include the absence of scratching in the newborn infant, the higher threshold of pruritus, the sometimes more important violence of scratching and finally the interactions between the children with pruritus and their parents. Two criteria are then suggested to evaluate the severity of pruritus, namely the alterations induced by the pruritus on the sleep and the presence of scratch marks. Atopic dermatitis, scabies, papular urticaria and dermatitis herpetiformis are the more severe and persistent skin diseases responsible for pruritus in children. The family history, the age of onset, the distribution of the lesions, the seasonal changes and the clinical course are useful in differentiating these diseases. Finally, the treatment with particular regard to the use of antihistamines was discussed.